Exploring the Impact of Artificial Intelligence on Supply Chain Management Performance: A Scoping Review - Eka Wahyu Kasih; Benardi Bernadi; Grace Yulianti (LPPM STIE Kasih Bangsa, 2024)
This scoping review examines the impact of Artificial Intelligence (AI) on Supply Chain Management (SCM) performance. Through a comprehensive analysis of existing literature, this study aims to elucidate the role of AI in enhancing SCM efficiency and effectiveness. Methodologically, a systematic search of scholarly databases was conducted, yielding a collection of relevant articles. Findings reveal a significant influence of AI on various aspects of SCM, including demand forecasting, inventory management, and logistics optimization. Moreover, AI-driven solutions demonstrate promising potential in mitigating supply chain disruptions and enhancing responsiveness to market dynamics. This review contributes to a deeper understanding of the transformative potential of AI in SCM, highlighting avenues for future research and practical implications for industry stakeholders.